Globalizacja a zagrożenia cywilizacyjne w Europie - refleksja moralna o ładzie społecznym = Globalization and threats of the civilization in Europe - the moral reflection about social order - Cynarski, Wojciech J. (Zielona Góra: Uniwersytet Zielonogórski)
The author raises questions and thesis about genetic relationships of civilization withaxiology. He pays attention to the moral crisis announces the fall of the culture. Christian ethics is the root of European civilization. Thus that all, which hits in his basis, is particularly dangerous for western (European, Latin) culture. It concerns then the threat for institution ofmarriage and family, the modern materialism, pressure of anti-Catholic ideologies (the feminism, neo-paganizm, secularization, Islamic fundamentalism) etc.
Keywords: globalizacja; zagrożenia cywilizacyjne; Europa